Ranade's economic writings - Bipan Chandra (New Delhi, 1990)
The present book is a testimony to the growing interest in an emerging field of sociology. Based on contributions from eminent social scientists, studies based on field investigations, the book includes studies of different professions such as teaching, medical, legal, social work and others written in Indian context.
Keywords: Land reforms